Interaction between the Arctic and Non-Arctic States in Scientific Research and Practical Development of the Geopolitical Potential of the Arctic - I. F. Kefeli; A. V. Nikolaenko (Administrative Consulting, 2022)
Aim. Reveal the methodological role of ideas about the geopolitical potential of the state in making managerial decisions in the development of the space of the Russian Arctic. The article presents an overview of fundamental research and articles by foreign authors that addresses the problem of realizing the geopolitical potential of the Arctic.Tasks. Development of the principles of geopolitical forecasting based on mathematical modeling of the geopolitical potential of the state and systematization of developments on the spatial development of the Russian Arctic as part of Greater Eurasia.Methods. Mathematical modeling of geopolitical processes, medium-term forecasting of the spatial development of the Russian Arctic in the face of challenges from foreign states claiming its natural resources and territorial waters.Results. It confirms the need to include scientific developments in the methodological apparatus of geopolitical research to identify qualitative and quantitative definitions of the geopolitical potential of the state, which contributes to ensuring the national security of Russia and improving its spatial development.Conclusions. The transition to the sixth technological mode is not limited to a radical transformation of the country’s production complex, but also implies the need to create a unified infrastructure architecture for the Greater Eurasia (“smart” Eurasia), into which the Russian Arctic organically fits.